Optimalisasi Potensi Desa Bresela melalui Pemberdayaan Masyarakat Guna Meningkatkan Perekonomian - Pasupati, Bayu; Dharmanegara, Ida Bagus Agung (Jurnal Pengabdian Masyarakat Berkarya, 2025)
Tourism in Bali is developing the concept of community-based tourist destinations that utilize the potential of nature, culture and local community life to attract tourists. Villages often have unique handicraft traditions, such as weaving, wickerwork or carving. The development of these creative industries can provide new economic opportunities through the marketing of local products, both in domestic and international markets. This activity is a Real Work Lecture Program - Community Empowerment by Students (KKN-PMM) 2024 by Warmadewa University with the local community of Brasela Village, Gianyar - Bali. The collaborative program of service activities carried out include: Education and Training, Economic Empowerment, Tourism Development, and Health and Environment. The results of the implementation of community service activities in the KKN-PMM program are quite enthusiastic in participating in the training, this can be seen from the responses from the UMKM players in Gianyar Village, Bali with the desire to be more creative in acquiring new skills that support the management of their business as well as choosing alternative digital-based marketing strategies to increase product competitiveness and reach new potential market targets.